2016
DOI: 10.1016/j.matlet.2016.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic properties of a porous polycarbonate material produced by additive manufacturing

Abstract: a b s t r a c tThis paper aims to investigate the acoustic properties of porous polycarbonate material (PPM) fabricated by additive manufacturing, and the feasibility to tailor artificial porous sound absorbing material is studied. Four PPM samples with different perforation angles were printed by using a 3D printer. Polycarbonate material was used, and the samples were printed with 25.4 micrometre layer resolution. Their sound absorption coefficient was experimentally measured using the two-microphone impedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 18 publications
2
59
0
Order By: Relevance
“…The obtained sound absorbing coefficients of the two metal foams in the frequency range of 100 Hz ~ 1000 Hz were shown in figure 2. It could be found that for the same material of metal foam, no matter copper foam or iron foam, the sound absorbing coefficients increased along with the increase of thickness from 5 mm to 30 mm in most detected frequency points, which was coincident with the results reported in the research of sound absorbing performances of the porous materials [13][14][15]. Meanwhile, it could be observed that the sound absorbing coefficients of the two metal foams in the low frequency range were low, and the maximum was no more than 40%.…”
Section: Pure Metal Foam Modesupporting
confidence: 86%
“…The obtained sound absorbing coefficients of the two metal foams in the frequency range of 100 Hz ~ 1000 Hz were shown in figure 2. It could be found that for the same material of metal foam, no matter copper foam or iron foam, the sound absorbing coefficients increased along with the increase of thickness from 5 mm to 30 mm in most detected frequency points, which was coincident with the results reported in the research of sound absorbing performances of the porous materials [13][14][15]. Meanwhile, it could be observed that the sound absorbing coefficients of the two metal foams in the low frequency range were low, and the maximum was no more than 40%.…”
Section: Pure Metal Foam Modesupporting
confidence: 86%
“…The Micro-Electro-Mechanical Systems were utilized to fabricate ultra-micro perforated MPPs for acoustic impedance and an absorption improvement [24]. Recently, Liu et al [25,26] introduced the 3D printing technique for high-precision and fast fabrication of MPPs as a pioneer. The Stereolithography Apparatus (SLA) was employed for MPP manufacturing to study the effects of the perforation angle and air gap distance on sound absorption [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu et al [25,26] introduced the 3D printing technique for high-precision and fast fabrication of MPPs as a pioneer. The Stereolithography Apparatus (SLA) was employed for MPP manufacturing to study the effects of the perforation angle and air gap distance on sound absorption [25]. Polyjet was applied to fabricate MPPs with different perforation ratios at a high-frequency range (1500-5500 Hz) and a high accuracy of the micro-circular perforations with a diameter of 0.6 mm was reported [26].…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic properties of an additively manufactured porous polycarbonate were evaluated by Liu et al [46]. Nansha and Hong [47] developed a micro-helix metamaterial by 3D printing and showed that helix vestibule and cavity depth had a significant impact on .…”
Section: Introductionmentioning
confidence: 99%